Doença do bico e das penas: avaliação em psitacídeos nativos apreendidos em Minas Gerais - Alessandra Vitelli de Aráújo (2011)
A study of psittacine beak and feather disease (PBFD) occurrence was conducted in parrots captive at a rescue and triage center for wild animals (CETAS-IBAMA), using genomic detection of PBFD virus (BFDV) DNA by PCR in blood (n=46), cloacal swab (n=144) or liver (n=140), being part of birds evaluated by more than one sample. Out of 190 birds studied, results indicated 12 positive for BFDV DNA, with a prevalence of 6.2% in Amazona aestiva (n=160) and 33.3% in Ara ararauna (n=3). No BFDV DNA was detected in livers of Aratinga leucophtalma, Pionus maximiliani, Guarouba guarouba, Amazona Amazonica, Amazona vinacea, Amazona rhodochoryta and Anodorhynchus hyacinthinus. In most cases alopecia was not associated to BFDV in liver. The histopathology of the livers was inconclusive. There were 98% similarity between sequences of strains isolated sites with sequences described in South Africa, Austria and Japan, may be strains of worldwide occurrence, potentially coming to Brazil with the legal and illegal trade of parrots. The sequences of Brazilian strains of BFDV BH 215 and BH 732 were deposited in GenBank. It was not possible to relate the BFDV infection with the geographical origin of birds. The rates of detection, although similar to other studies, indicate for a tendency of elevation, possibly associated to the stress and bird concentration in captivity.